Targeting Mechano-Transcription Process as Therapeutic Intervention in Gastrointestinal Disorders - Geesala, Ramasatyaveni; Lin, You-Min; Zhang, Ke; Shi, Xuan-Zheng (Frontiers in Pharmacology, 2021)
Mechano-transcription is a process whereby mechanical stress alters gene expression. The gastrointestinal (GI) tract is composed of a series of hollow organs, often encountered by transient or persistent mechanical stress. Recent studies have revealed that persistent mechanical stress is present in obstructive, functional, and inflammatory disorders and alters gene transcription in these conditions. Mechano-transcription of inflammatory molecules, pain mediators, pro-fibrotic and growth factors has been shown to play a key role in the development of motility dysfunction, visceral hypersensitivity, inflammation, and fibrosis in the gut. In particular, mechanical stress-induced cyclooxygenase-2 (COX-2) and certain pro-inflammatory mediators in gut smooth muscle cells are responsible for motility dysfunction and inflammatory process. Mechano-transcription of pain mediators such as nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF) may lead to visceral hypersensitivity. Emerging evidence suggests that mechanical stress in the gut also leads to up-regulation of certain proliferative and pro-fibrotic mediators such as connective tissue growth factor (CTGF) and osteopontin (OPN), which may contribute to fibrostenotic Crohn’s disease. In this review, we will discuss the pathophysiological significance of mechanical stress-induced expression of pro-inflammatory molecules, pain mediators, pro-fibrotic and growth factors in obstructive, inflammatory, and functional bowel disorders. We will also evaluate potential therapeutic targets of mechano-transcription process for the management of these disorders.